Interview with Esther Teichmann, artist, Kennington, London, 21 September 2013 - Messham-Muir, Kit (2014)
Part 2: Interview with Esther Teichmann, artist, Kennington, London, 21 September 2013 Esther Teichmann is a photographic artist whose works are richly poetic and potentially affecting. Her images are often beautifully shot and seductive, yet carry a sense of foreboding. I met Esther shortly after she had returned to London after a period of teaching at CalArts. In this interview we discuss the affective dimensions of darkness, and the tensions of absence/presence and life/loss that are often held in photographic images of the body. This is a two-part interview. Dr Kit Messham-Muir The University of Newcastle